PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN YANG BERDAMPAK PADA KEPUASAN KONSUMEN (STUDI PADA PRODUK HANDUK LUPPEN DI TOKO SUMBER HIDUP) - Suharto (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
The purpose of this study was to determine the relationship between price, product quality, purchasing decisions, and consumer satisfaction. Consumer decisions in purchasing are determined by the buyer, marketing stimulation, and other stimulation. These variables influence the buying process each other to produce purchasing decisions based on price, brand choice, preferred store, and the number of purchases. One of the components that must be considered to influence consumers in purchasing is providing products with competitive prices and product quality. The data analysis technique used is the path analysis technique, this research uses quantitative qualitative methodsusing the numbers obtained through the questionnaire. This method is used for data obtained from questionnaire answers in the form of numbers that have been classified into specific categories using tables to facilitate testing through multivariate Structural Equation Modeling (SEM) techniques to determine the relationship between variables X Y and Z. The results of this study found that the price variable has no significant effect on purchasing decisions and consumer satisfaction. Product quality variables have a substantial effect on purchasing decisions and consumer satisfaction. The price variable has no significant effect on consumer satisfaction through purchasing decisions. And the product quality variable has a significant effect on consumer satisfaction through purchasing decisions